Monoclonal gammopathy-associated C3 glomerulonephritis secondary to follicular lymphoma: a case report - Cai, Wenjing; Guo, Hanguo; Zhang, Minghui; Liang, Huaban; Liang, Xinling; Wang, Yihan; Shi, Qingying; Ye, Zhiming; Li, Zhilian (Frontiers in Immunology, 2025)
C3 glomerulopathy encompasses a group of glomerular diseases characterized by the predominant deposition of complement component C3 on kidney biopsy without significant immunoglobulin staining. Monoclonal gammopathy (MIg)-associated C3 glomerulopathy is considered a distinct subtype. We report a case of a 38-year-old male with a history of HBV infection who presented with a left neck mass, hematuria, proteinuria, elevated creatinine, normal complement level, and an IgM kappa M-spike on serum immunofixation electrophoresis. He was diagnosed with follicular lymphoma-associated MIg-C3 glomerulonephritis (MIg-C3GN), accompanied by extensive infiltration of lymphoma cells in the renal interstitium. Kidney immunohistochemistry was positive for CD19 and CD20 (B-cell markers), as well as CD10 and Bcl2, confirming the follicular lymphoma subtype. Within the areas of lymphoma cell infiltration, immunohistochemistry was also positive for IgM and kappa light chains but negative for lambda light chains, consistent with the serum electrophoresis findings. Positive autoantibodies to complement C3 convertase and complement factor H indicated complement dysregulation. The patient successively underwent various chemotherapy and targeted therapy regimens. During nearly 2 years of follow-up, renal outcomes were favorable, with resolution of hematuria and proteinuria and normalization of renal function, suggesting that lymphoma-directed therapy can improve renal outcomes in MIg-C3GN. However, the patient achieved partial remission but later relapsed and progressed, with suspicion of transformation into diffuse large B-cell lymphoma.